Effect of maleic anhydride grafted polylactic acid concentration on mechanical and thermal properties of thermoplasticized starch filled polylactic acid blends. Issue 9 (November 2021) - Chauhan, Shakti; Raghu, N; Raj, Anand
Polylactic acid (PLA) is blended with native starch or thermo plasticized starch (TPS) for preparing biodegradable composites. However, poor compatibility of PLA with starch results in the composites with inferior mechanical properties. This study examines the effect of Maleic Anhydride-Grafted-PLA (GMAPLA) coupling agent and its concentration on the extent of improvements in mechanical and thermal properties of PLA –TPS blends. Maleic anhydride was grafted on PLA in Haake torque rheometer, characterized and used as the coupling agent. PLA/TPS (wt/wt) blends (70/30 and 50/50) were prepared by twin screw extrusion. GMAPLA at three different levels 5%, 10% and 15% (wt%) with respect to PLA content was taken to study its effect on mechanical properties of blends. Presence of GMAPLA significantly improved the mechanical properties (tensile, flexural and impact strength) of TPS/PLA blends. Among the three concentrations, 10% GMAPLA in the blend was found to give the maximum improvement in strength properties. Dynamic mechanical analysis and thermo-gravimetric analysis indicated no significant effect of GMAPLA content on transition temperatures and thermal degradation behavior of the blends.